2022
DOI: 10.3390/rs14205241
|View full text |Cite
|
Sign up to set email alerts
|

Early Monitoring of Cotton Verticillium Wilt by Leaf Multiple “Symptom” Characteristics

Abstract: Early diagnosis of cotton verticillium wilt (VW) and accurate assessment of the disease degree are important prerequisites for preventing the large-scale development of cotton VW. Hyperspectral techniques have been widely used for monitoring the extent of plant diseases, but early detection of VW disease in cotton remains a challenge. In this study, the Boruta algorithm was used to select the key physiological characteristics (leaf temperature, chlorophyll a content, and equivalent water thickness) of cotton l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 46 publications
1
5
0
1
Order By: Relevance
“…3 revealed a more pronounced decline in VW3 than that in VW4. This finding is consistent with previous studies that conducted physicalchemical experiments on leaves exposed to various stress levels, which concluded that chlorophyll content was lower in more severely stressed leaves [6], [44], [45]. This is also evident in Fig.…”
Section: A Effects Of Vw On Cotton Canopysupporting
confidence: 93%
See 2 more Smart Citations
“…3 revealed a more pronounced decline in VW3 than that in VW4. This finding is consistent with previous studies that conducted physicalchemical experiments on leaves exposed to various stress levels, which concluded that chlorophyll content was lower in more severely stressed leaves [6], [44], [45]. This is also evident in Fig.…”
Section: A Effects Of Vw On Cotton Canopysupporting
confidence: 93%
“…Therefore, we separated PAR as an independent factor and combined fPAR and fesc to represent non-physiological state of plant. In this study, we used NIRv and FCVI to approximate the characterization of fPAR×fesc [32], [33], [34], then (1) convert into (6).…”
Section: Parameter Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Mechanical approaches are particularly useful for fibre quality and fibre yield [ 1 ]. Interestingly, in recent years an increasing number of digital methods to capture detailed plant information have been developed, utilizing RGB cameras [ 2 8 ], hyperspectral sensors [ 9 11 ], thermal cameras [ 1 , 12 ], and LiDAR-based sensors [ 13 , 14 ]. These techniques offer unique advantages for characterizing various cotton plant phenotypes, can be non-destructive, and enable higher throughput applications.…”
Section: Introductionmentioning
confidence: 99%
“…These methods are destructive and relatively time-consuming. With the advancement of technology, some non-destructive detection techniques have been brought up, such as hyperspectral imaging and thermal imaging ( Poblete et al., 2021 ; Yang et al., 2022 ). However, they can only detect VW based on symptoms in the above-ground parts of the plant.…”
Section: Introductionmentioning
confidence: 99%